In-depth Analysis of Adultcentrism in the Educational Field: Tensions in the Face of Childhood Protagonism - Lay-Lisboa, Siu (2022)
Aim. This research proposes deeply analyzing the interactions between adultcentrism and the exercise of childhood protagonism in educational contexts. Method. The methodological de-sign assumes elements from Participatory Action Research through dialogic strategies of in-formation production, such as graphic, spatial techniques, social theatre, discussion groups, and interviews of adults. Twenty-one people participated in this research project, four teach-ers and 15 students between 10 and 12 years old from a school in Chile. The dimensions of analysis were adultcentrism, protagonism of childhood, relationships between adulthood and childhood, and gender diversity. The data analysis was based on the process of open, axial, and selective coding, allowing the emergence of new categories. Results. The research find-ings show that the main category is the interaction between adultcentrism and protagonism. This category is expressed in 5 subcategories: power relations, organization and decision-making, diversities, treatment and affections, technologies in dispute, and perspective and gender stereotypes. Conclusions and recommendations. The research promotes more open and democratic classroom practices in the education field, allowing the teaching staff to gen-erate collaborative work co-constructed and situated to encourage childhood autonomy. In its practical implications, this research allows considering the opinions of childhood in the elabo-ration of the plans that schools in Chile must implement, such as school connivance and citi-zen training plans.